The Role of Schools in Improving Physical Motor Development of Children in Learning at SD Negeri 2 Wlahar Purbalingga Regency - Slamet Waluyo; Ine Kusuma Aryani (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This study employs a literature review method by examining various articles and books. The purpose of this research is to determine the physical motor development of children at SD Negeri 2 Wlahar, Purbalingga Regency, and to describe the role of schools in enhancing children's physical motor development. In addition to the literature review, data collection methods in this study include observation, interviews, and documentation. This research adopts a descriptive approach to explain the phenomena or events observed in the field. The subjects of this study were 68 students from grades 4 to 6. Data analysis techniques utilized in this study include pre-field and field analysis using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. The results indicate that all students exhibit varying levels of physical motor development, which continuously evolves according to their learning activities. Schools play a crucial role in fostering the motor development of their students.